Status for Land Rights Ulayat After The Enactment of The Agrarian Constitution - Abdul Hamid Usman (International Journal Reglement & Society (IJRS), 2021)
The right of ulayat is the right of the legal alliance to freely use lands that are still forests within its territory, for the benefit of the legal alliance itself and its members, or for the benefit of outsiders (immigrants, foreigners) but with its permission and always with the payment of recognition of recognition, in which the legal alliance continues to intervene,  hard or not, also on the land that has been cultivated by people who are located in the environment of his territory.The right of ulayat as the right of indigenous peoples to land, recognized its position by uupa, as stated in Article 3, which stipulates that ulayat rights and similar rights of indigenous law communities can still be implemented by the indigenous law community concerned as long as the ulayat rights in reality still exist. Based on the discussion, it can be concluded that the status of the land of ulayat rights after the enactment of the Agrarian Basic Law is related to whether or not the ulayat rights themselves exist. Against the right of ulayat which in reality still exists, the status of the land of the ulayat rights is still as it was before the enactment of the Agrarian Principal Law, that is for the purposes of legal federation, for the purposes of members of the legal federation, and for non-members of the legal federation, the latter on condition of paying the recognition money. Against ulayat rights which in reality no longer exist, the status of land rights is changed to the purposes of the nation and the State, under the authority to govern by the State, in this case the Government of the Republic of Indonesia and is run by the Regional Government